2017
DOI: 10.1177/1940082917733230
|View full text |Cite
|
Sign up to set email alerts
|

Change in Soil Microbial Community Compositions and Diversity Following the Conversion of Tropical Forest to Rubber Plantations in Xishuangbanan, Southwest China

Abstract: The ecological consequences of converting tropical forests to rubber plantations on the soil microbial compositions and diversity remain unknown. By using an Illumina MiSeq sequencing analysis, we assessed the compositions and diversity of bacterial and fungal community in soils of rubber plantation (or rubber forest, RF), secondary tropical forest (STF), and tropical seasonal rainforest (TSR) in Xishuangbanna, southwest China. Our findings revealed that (a) for bacterial composition, Bacillaceae was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The increase in bacterial alpha diversity following conversion to agriculture is consistent with earlier work using pre-next generation sequencing approaches (da Jesus et al, 2009), and is in contrast to commonly reported decreases in the diversity of plants (Ibrahim et al, 2003), animals (Brook et al, 2003;Gardner et al, 2009;Lim, 2017), and fungi (Mueller et al, 2014;McGuire et al, 2015;Kerfahi et al, 2016;Lan et al, 2017;Cai et al, 2018), following agricultural conversion. This may result from ecological differences between bacteria and eukaryotes; for example, bacterial diversity may respond to changes in soil chemical properties, rather than being directly affected by land use change.…”
Section: Diversitysupporting
confidence: 88%
“…The increase in bacterial alpha diversity following conversion to agriculture is consistent with earlier work using pre-next generation sequencing approaches (da Jesus et al, 2009), and is in contrast to commonly reported decreases in the diversity of plants (Ibrahim et al, 2003), animals (Brook et al, 2003;Gardner et al, 2009;Lim, 2017), and fungi (Mueller et al, 2014;McGuire et al, 2015;Kerfahi et al, 2016;Lan et al, 2017;Cai et al, 2018), following agricultural conversion. This may result from ecological differences between bacteria and eukaryotes; for example, bacterial diversity may respond to changes in soil chemical properties, rather than being directly affected by land use change.…”
Section: Diversitysupporting
confidence: 88%
“…The values in our and similar sites contrast to soils where Shannon's diversity indices typically exceeded 6. For example, values from 6.90 to 7.31 were measured in the Loess Plateau, China (Zeng et al, 2016), and values over 5 are typically found in diverse seasonal and tropical forest soils in southwest China (Lan et al, 2017). Even polar desert soils can host communities with Shannon's diversity indices exceeding 8 (McCann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in bacterial alpha diversity following conversion to agriculture differs sharply with commonly reported decreases in the diversity of plants (Ibrahim et al, 2003), animals (Bierregaard, 2001; Brook, Sodhl, & Ng, 2003; Gardner et al, 2009) and fungi (Cai, Zhang, Yang, & Wang, 2018; Kerfahi, Tripathi, Dong, Go, & Adams, 2016; Lan et al, 2017; McGuire et al, 2015; Mueller et al, 2014). This difference may result from ecological differences between bacteria and eukaryotes; for example, bacterial diversity may respond to changes in soil chemical properties, rather than being directly affected by land use change.…”
Section: Discussionmentioning
confidence: 67%